THU0290 Peripheral mononuclear cells of systemic juvenile idiopathic arthritis patients have no intrinsic defect in interferon-gamma signaling. (23rd January 2014) - Put, K.; Avau, A.; Mitera, T.; Put, S.; Bader-Meunier, B.; Quartier, P.; Wouters, C.; Matthys, P.
Abstract : Background: Systemic juvenile idiopathic arthritis (sJIA) is one of the most severe pediatric systemic immune-inflammatory disorders, characterized by arthritis and systemic features including fever, rash, lymphadenopathy and leukocytosis. A frequent, potentially fatal complication of sJIA is macrophage activation syndrome (MAS). An excessive production of pro-inflammatory cytokines has been demonstrated in sJIA with or without MAS, yet the exact cause and pathogenesis are still unknown. Studies on gene expression profiles performed on freshly isolated peripheral blood mononuclear cells (PBMCs) from sJIA patients revealed a conspicuous absence of interferon-gamma (IFN-γ)-upregulated genes. This is a peculiar finding, given the highly inflammatory nature of sJIA and the concept that IFN-γ is a driver of MAS. Objectives: In this study we explored whether PBMCs of sJIA patients have a defect in IFN-γ signaling by studying induced genes and proteins upon in vitro stimulation with IFN-γ. Methods: 9 sJIA patients (7 under treatment and in remission, 1 with active disease despite treatment, 1 untreated) and 1 sJIA patient presenting with MAS were recruited from the University Hospital of Leuven after giving informed consent. PBMCs from patients and healthy controls were obtained by gradient centrifugation and were cultured for 24 hours in the presence or absence of IFN-γ. RNA was extracted from the harvested cells. cDNA was synthesized and qPCR was performed on different IFN-γ-induced genes. IFN-γ-induced proteins (interferon-induced protein (IP-10) and monocyte chemotactic factor-1 (MCP-1)) were analyzed in supernatant of cells, by ELISA. Results: In PBMCs from healthy control patients, IFN-γ induced - as expected - upregulation of STAT 1 mRNA, an important IFN-γ-induced transcription factor, as well as other IFN-γ-induced genes such as indoleamine 2, 3-dioxygenase (IDO) and IP-10. Some genes such as suppressor of cytokine signaling 3 (SOCS3), MCP-1 and interferon regulatory factor-1 (IRF-1) were not upregulated in healthy PBMCs. Most importantly, all of the IFN γ-associated genes that were significantly induced in healthy control PBMCs were at the least equally well induced in sJIA patients (in both treated, untreated and MAS conditions). Significant production of IP-10 protein was found in the supernatant of IFN-γ-stimulated PBMCs, and here again there was no difference between patients and controls. Conclusions: We conclude that PBMCs from sJIA/MAS patients have no intrinsic defect in the IFN-γ machinery. Thus the absence of an IFN-γ signature in sJIA, as reported in gene expression studies, cannot be explained by decreased in vitro responsiveness of PBMCs to IFN-γ, and further research is required to explain this discrepancy. Disclosure of Interest: None Declared